2017
DOI: 10.1186/s12985-017-0763-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of triple antibody sandwich enzyme-linked immunosorbent assays for begomovirus detection using monoclonal antibodies against Tomato yellow leaf curl Thailand virus

Abstract: Background Tomato yellow leaf curl Thailand virus, TYLCTHV, is a begomovirus that causes severe losses of tomato crops in Thailand as well as several countries in Southeast and East Asia. The development of monoclonal antibodies (MAbs) and serological methods for detecting TYLCTHV is essential for epidemiological studies and screening for virus-resistant cultivars.MethodsThe recombinant coat protein (CP) of TYLCTHV was expressed in Escherichia coli and used to generate MAbs against TYLCTHV through hybridoma te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…A study showed the detection of various plant viruses, such as the Squash mosaic virus (SQMV), Cowpea severe mosaic virus (CPSMV), Cucumber mosaic virus (CMV), Cowpea aphid borne mosaic virus (CABMV), Zucchini yellow mosaic virus (ZYMV), and Papaya lethal yellowing virus (PLYV) in squash, cowpea, and papaya plants [ 61 ]. The detection of Tomato yellow leaf curl Thailand virus, (TYLCTHV) in tomato, pepper, eggplant, okra, and cucurbit plants was analyzed using a TAS-ELISA (triple antibody sandwich enzyme-linked immunosorbent assays) [ 62 ]. The Protein A sandwich enzyme-linked immunosorbent assay (PAS-ELISA) has been used for the detection of various Badnaviruses in West African yam plants [ 63 ].…”
Section: Methods For Plant Viral Diagnosticmentioning
confidence: 99%
“…A study showed the detection of various plant viruses, such as the Squash mosaic virus (SQMV), Cowpea severe mosaic virus (CPSMV), Cucumber mosaic virus (CMV), Cowpea aphid borne mosaic virus (CABMV), Zucchini yellow mosaic virus (ZYMV), and Papaya lethal yellowing virus (PLYV) in squash, cowpea, and papaya plants [ 61 ]. The detection of Tomato yellow leaf curl Thailand virus, (TYLCTHV) in tomato, pepper, eggplant, okra, and cucurbit plants was analyzed using a TAS-ELISA (triple antibody sandwich enzyme-linked immunosorbent assays) [ 62 ]. The Protein A sandwich enzyme-linked immunosorbent assay (PAS-ELISA) has been used for the detection of various Badnaviruses in West African yam plants [ 63 ].…”
Section: Methods For Plant Viral Diagnosticmentioning
confidence: 99%
“…The identity and orientation of the SLCMV-CP gene in the resulting plasmid was confirmed by DNA sequence analysis. The recombinant SLCMV-CP was expressed, purified and analyzed as previously described [ 31 ]. Briefly, a bacterial clone containing the correct recombinant plasmid was grown at 37 °C in LB medium containing 100 µg/ml ampicillin to an absorbance at 600 nm (OD 600 ) of 0.6.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant SLCMV-CP was purified using a Ni–NTA agarose resin column (QIAGEN, Germany) under denaturing conditions following the manufacturer’s recommendations. Purified proteins were analyzed by 12% sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and confirmed by western blotting using a commercial MAb to SLCMV (DSMZ, Germany) and MAb D2, which broadly reacts with begomoviruses [ 31 ]. The purified SLCMV-CP was dialyzed against phosphate-buffered saline (PBS), pH 7.4, before being used for mouse immunization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to ELISA, dot blots and western blots have also been used to detect infection, which primarily include an antibody-based detection of the virus in tissue lysates that are either directly blotted or separated and transferred from a protein gel onto a nitrocellulose membrane [22]. [35] * Antiserum was used for detection in ELISA.…”
Section: Detection Of Infectionmentioning
confidence: 99%